2019
DOI: 10.1186/s12874-019-0857-y
|View full text |Cite|
|
Sign up to set email alerts
|

Challenges of one-year longitudinal follow-up of a prospective, observational cohort study using an anonymised database: recommendations for trainee research collaboratives

Abstract: BackgroundTrainee research collaboratives (TRCs) have pioneered high quality, prospective ‘snap-shot’ surgical cohort studies in the UK. Outcomes After Kidney injury in Surgery (OAKS) was the first TRC cohort study to attempt to collect one-year follow-up data. The aims of this study were to evaluate one-year follow-up and data completion rates, and to identify factors associated with improved follow-up rates.MethodsIn this multicentre study, patients undergoing major gastrointestinal surgery were prospectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…This study delves into the comparisons of preoperative GNRI and NLR between the AKI and NAKI groups. The substantial decrease in preoperative GNRI and the notable increase in NLR among AKI patients are consistent with the study’s hypothesis and align with existing literature linking poor nutritional status and heightened inflammatory response to adverse postoperative outcomes, including AKI ( 23 ).…”
Section: Discussionsupporting
confidence: 90%
“…This study delves into the comparisons of preoperative GNRI and NLR between the AKI and NAKI groups. The substantial decrease in preoperative GNRI and the notable increase in NLR among AKI patients are consistent with the study’s hypothesis and align with existing literature linking poor nutritional status and heightened inflammatory response to adverse postoperative outcomes, including AKI ( 23 ).…”
Section: Discussionsupporting
confidence: 90%
“…First, there was a moderate attrition of patients from recruitment to 1-year follow-up. However, this was largely related to centre non-participation and there was no suggestion of residual attrition bias 18 . The high rate of open surgery included may explain the marginally higher rates of malignant pathology and major 30-day postoperative complications observed compared with the original cohort.…”
Section: Discussionmentioning
confidence: 92%
“…To facilitate changes in research team members over the 1-year interval from recruitment to follow-up, patient-identification numbers were stored centrally using a secure REDCap (Research Electronic Data Capture) server 17 , or on a password-protected NHS computer according to local Caldicott Guardian requirement. The full methodology for long-term follow-up in this study has been reported previously 18 . In brief, all participating centres were invited to submit 1-year follow-up data for patients included in the original cohort study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies adopting this collaborative cohort study methodology have achieved high levels of case ascertainment and data accuracy with external validation 15 , 16 . In the present study, low-volume centres (fewer than 5 patients per specialty group) were identified, and reviewed independently to confirm complete case ascertainment.…”
Section: Methodsmentioning
confidence: 99%